Electrodeposition of bactericidal and bioactive nano-hydroxyapatite onto electrospun piezoelectric polyvinylidene fluoride scaffolds. Issue 23 (14th December 2020) - Rodrigues, Pedro J. G.; Elias, Conceição de M. V.; Viana, Bartolomeu C.; de Hollanda, Luciana M.; Stocco, Thiago D.; de Vasconcellos, Luana M. R.; Mello, Daphne de C. R.; Santos, Francisco E. P.; Marciano, Fernanda R.; Lobo, Anderson O.
Abstract: Abstract : The fibrous scaffolds for bone tissue engineering that mimic the extracellular matrix with bioactive and bactericidal properties could provide adequate conditions for regeneration of damaged bone. Electrospun ultrathin fiber covered with nano-hydroxyapatite is a favorable fibrous scaffold design. We developed a fast and reproducible strategy to produce polyvinylidene fluoride (PVDF)/nano-hydroxyapatite (nHAp) nanofibrous scaffolds with bactericidal and bioactive properties. Fibrous PVDF scaffolds were obtained first by the electrospinning method. Then, their surfaces were modified using oxygen plasma treatment followed by electrodeposition of nHAp. This process formed nanofibrous and superhydrophilic PVDF fibers (133.6 nm, fiber average diameter) covered with homogeneous nHAp (202.6 nm, average particle diameter) crystals. Energy-dispersive X-ray spectrometry demonstrated the presence of calcium phosphate, indicating a Ca/P molar ratio of approximately 1.64. X-ray diffraction, Fourier transform infrared spectroscopy, and Raman spectroscopy spectra identified β-phase of nHAp. Thermal analysis indicated a slight reduction in stability after nHAp electrodeposition. Bactericidal assays showed that nHAp exhibited 99.8% efficiency against Pseudomonas aeruginosa bacteria. The PVDF/Plasma and PVDF/nHAp groups had the highest cell viability, total protein, and alkaline phosphatase activity by 7 days after exposure of the scaffolds to MG63 cell culture. Therefore, the developed scaffolds are an exciting alternative for application in bone regeneration.